(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
The study of the shell microstructure of brachiopods is fundamental to understand their evolutionary history and their biomineralization process. Here, species of forty Lopingian brachiopods genera, representative of twenty-seven different families, are investigated using the Scanning Electron Microscope. The investigated specimens come from different paleogeographic localities in the Palaeotethys/Neotethys oceans. The studied brachiopods show a large variability of the shell fabric, which is mainly related to the organization of its structural units: laminae, fibers and columns, possibly crossed by pseudopunctae or punctae. For the Strophomenata, the laminar fabric of Productida is crossed by pseudopunctae with taleolae and the laminae are often organized in packages, with the blades oriented about perpendicular to each other; this feature is less evident in the laminar Orthotetida, which bear pseudopunctae without taleoae. For the Rhynchonellata, fibrous fabrics are either impuctate in the Spiriferida, most Athyridida and Rhynchonellida, or with punctae, as observed in the Orthida, Terebratulida and in the Neoretziidae (Athyridida). The fibers show a range of sizes and shapes also in the same specimens and the transition to the columnar layer is different than in Strophomenata. The arrangement of the structural units revealed that the disposition of the organic membranes, on which biomineralization took place, was highly variable among the taxa. On the other hand, two distinctive features are analogous among distantly related groups, i.e. the Strophomenata and the Rhynchonellata: the presence of a columnar tertiary layer underlying the secondary fabric and the alternations between fibers/laminae of the secondary layer and columns of the tertiary layer. This suggests that there are common factors controlling the development and evolution of the shell fabric in all rhynchonelliformean brachiopods that can be linked to their taxonomical position, to their environmental requirements and to constraints imposed by their low-energy life-style. This should be taken into account to understand how these calcifying organisms responded and will respond to environmental and climate change in past and future times.